Ответы и объяснения

2013-05-08T07:06:05+00:00

х-6у=-2                  х=6у-2

2х+3у=11              2(6у-2) + 3у = 11

2(6у-2)+3у=11

12у-4+3у=11

12у+3у=11+4

15у=15

у=15/15

у=1

х=6*1-2=4

Ответ. (4;1)

 

2х+у=-5       у=-5-2х

х-3у=-6       х-3(-5-2х)=-6

х-3(-5-2х)=-6

х+15+6х=-6

7х=-21

х=-3

у=-5-2*(-3) = -5+6=1

Ответ. (-3;1) 

2013-05-08T07:35:07+00:00

способом сложения:

x-6y= -2 / *(-2)

2x+3y=11

-2x+12y=4

2x+3y=11

15y=15

y=1

x=4

Ответ: (4;1)

2x+y=-5 /*3

x-3y=-6

6x+3y=-15

x-3y=-6

7x=-21

x=-3

y=1

Ответ: (-3;1)